1981
DOI: 10.1002/tera.1420230312
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the teratogenicity and mutagenicity of cyclophosphamide with thiol compounds

Abstract: Cyclophosphamide must be metabolized to have either therapeutic or toxic effects; many of the major metabolites of cyclophosphamide interact with thiol compounds. To characterize the relationship between the teratogenic and mutagenic metabolites of cyclophosphamide, the effect of thiol compounds on the teratogenicity and mutagenicity of this drug was studied. The effect on teratogenicity was assessed in vivo by treatment of rats with thiol compounds or thiol‐depleting agents prior to administration to cyclopho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 22 publications
1
8
0
1
Order By: Relevance
“…Since the present study is presumably the first report to show that PBO decreases CYP2B activity by suppressing the expression of its mRNA, an additional study to clarify the direct effect of PBO, including the reversible or irreversible manner of inhibition, on this enzyme activity is warranted. On the other hand, previous reports have indicated that oxidative stress is a significant factor contributing to cyclophosphamide-induced fetal malformations, which are substantially attenuated by antioxidants, such as glutathione, cysteine, and indole-3-carbinol, but exacerbated by glutathione depletion (Hales, 1981;Slott and Hales, 1987;Han et al, 1995;Bailey et al, 2005). Recently, we demonstrated that butylated hydroxyanisole, a synthetic antioxidant food additive, markedly reduced the incidence and severity of fetal defects induced by cyclophosphamide in rats and mice (Kang et al, 2003;Kim et al, 2003).…”
Section: Discussionmentioning
confidence: 95%
“…Since the present study is presumably the first report to show that PBO decreases CYP2B activity by suppressing the expression of its mRNA, an additional study to clarify the direct effect of PBO, including the reversible or irreversible manner of inhibition, on this enzyme activity is warranted. On the other hand, previous reports have indicated that oxidative stress is a significant factor contributing to cyclophosphamide-induced fetal malformations, which are substantially attenuated by antioxidants, such as glutathione, cysteine, and indole-3-carbinol, but exacerbated by glutathione depletion (Hales, 1981;Slott and Hales, 1987;Han et al, 1995;Bailey et al, 2005). Recently, we demonstrated that butylated hydroxyanisole, a synthetic antioxidant food additive, markedly reduced the incidence and severity of fetal defects induced by cyclophosphamide in rats and mice (Kang et al, 2003;Kim et al, 2003).…”
Section: Discussionmentioning
confidence: 95%
“…In another model, pregnant rats are dosed on gestation day 13 with 12.5 mg/kg of CPA (morning of plug=0). Remarkably, in this paradigm such treatments induce encephalocele at a rate of 96% despite the neural tube having closed on approximately gestation 11 (Zhao et al, 2010). This observation contradicts our previous concept about windows of susceptibility, which posit that such neural tube defects should no longer occur after the neural tube has closed.…”
Section: Cyclophosphamide Teratogenicitymentioning
confidence: 99%
“…In contrast, the intervention treatment plus CPA had the opposite effects on the number of cells expressing Blc‐2 and Bax. Based upon literature reports and maternal NOT embryonic measures of oxidative stress, Zhao et al (2010) suggest the amelioration of CPA's effects are the result of the antioxidant properties of soy isoflavones and folic acid. It is the reviewer's opinion that there may be another explanation.…”
Section: Cyclophosphamide Teratogenicitymentioning
confidence: 99%
“…On the other hand, oxidative stress is also a significant factor contributing to cyclophosphamide‐induced fetal malformations. This is substantially attenuated by antioxidants, such as glutathione, cysteine, and indole‐3‐carbinol, but exacerbated by glutathione depletion (Hales, 1981; Slott and Hales, 1987; Han et al, 1995; Bailey et al, 2005). We demonstrated that butylated hydroxyanisole, a synthetic antioxidant food additive, markedly reduced the incidence and severity of fetal defects induced by cyclophosphamide in rats and mice (Kang et al, 2003; Kim et al, 2003).…”
Section: Introductionmentioning
confidence: 99%